1977
DOI: 10.1128/aac.11.4.735
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Factor Produced by Haemophilus influenzae b: Partial Purification of the Factor and Transfer of Its Genetic Determinant

Abstract: When aerobically grown on complex media, Haemophilus influenzae b and unencapsulated variants, Rb strains, produced a bactericidal factor that was active against other Haemophilus species and certain genera of the Enterobacteriaceae. A total of 341 clinical isolates of Haemophilus were tested for susceptibility to the factor. Ninety-three percent of H. influenzae (nontypable), 75% of H. haemolyticus, 71% of H. parainfluenzae, and 22% of H. parahaemolyticus were susceptible. H. influenaze b strains were resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Preliminary characterization suggested that the bacteriocin haemocin was a thermostable protein molecule of between 10,000 and 14,000 daltons based on sodium dodecyl sulfategel electrophoresis (11). It was not a "colicinlike" bacteriocin in that it was not inducible by ultraviolet radiation or treatment with mitomycin C, had a wide range of activity, and did not kill by "single-hit" kinetics.…”
mentioning
confidence: 99%
“…Preliminary characterization suggested that the bacteriocin haemocin was a thermostable protein molecule of between 10,000 and 14,000 daltons based on sodium dodecyl sulfategel electrophoresis (11). It was not a "colicinlike" bacteriocin in that it was not inducible by ultraviolet radiation or treatment with mitomycin C, had a wide range of activity, and did not kill by "single-hit" kinetics.…”
mentioning
confidence: 99%
“…Haemophilus influenzae b and exhibits bactericidal activity against Haemophilus species and certain members of the Enterobacteriaceae family (9,10). We previously have shown that its mode of action involves the inhibition of deoxyribonucleic acid synthesis in both H. influenzae Rd strain C25 and Escherichia coli CR34 (6).…”
Section: The Bacteriocin Haemocin Is Produced Bymentioning
confidence: 99%
“…Haemocin is bactericidal for H. influenzae types a, c, d, e, and f, other Haemophilhs species, and certain members of the Enterobactericeae family (9,10 In a previous report we demonstrated that survival curves of strain C25 treated with haemocin were not consistent with a single-hit mechanism of killing because of the shoulder obtained in the initial portion of the curves (10). However, the survival curves of strain CR34 treated with haemocin appeared to be different from those of strain C25 under similar conditions.…”
Section: The Bacteriocin Haemocin Is Produced Bymentioning
confidence: 99%
“…Primer extension analysis revealed a putative transcriptional start site 34 bp upstream of the start codon, and the presence of a promoter immediately upstream of hmcI was confirmed by cloning the gene into a promoterless chloramphenicol acetyltransferase vector. To characterize the hmcI gene product, a His-HmcI fusion protein was constructed.Most type b-encapsulated strains of Haemophilus influenzae, including strains demonstrated to be genetically diverse by multilocus enzyme electrophoresis (22), produce the bacteriocin haemocin (HMC), which is toxic in vitro to virtually all non-type b strains of H. influenzae, both encapsulated and nonencapsulated (16,37,38). Data suggest that HMC exerts its toxicity by inhibiting DNA synthesis in susceptible strains (34); however, little is known about the genetic determinants conferring HMC production or immunity in H. influenzae.…”
mentioning
confidence: 99%
“…Most type b-encapsulated strains of Haemophilus influenzae, including strains demonstrated to be genetically diverse by multilocus enzyme electrophoresis (22), produce the bacteriocin haemocin (HMC), which is toxic in vitro to virtually all non-type b strains of H. influenzae, both encapsulated and nonencapsulated (16,37,38). Data suggest that HMC exerts its toxicity by inhibiting DNA synthesis in susceptible strains (34); however, little is known about the genetic determinants conferring HMC production or immunity in H. influenzae.…”
mentioning
confidence: 99%